Climate-influenced performance and offspring development of merino sheep in a dry temperate-cold valley - Villagra, Edgar Sebastian (2024)
This study aims to explore the effects of climate on the performance and offspring development of aged Merino sheep relocated from an arid, cold environment with harsh grazing conditions to a dry, temperate-cold valley with irrigated pasture production. We utilized time series data from merino sheep in a dry temperate-cold climate in southern Argentina to characterize their growth curves, assess the impact of climate on performance, and compare offspring growth with maternal growth. Our approach involved developing a dynamic model, a non-autonomous differential equation growth curve based on the widely used Brody model. The model considered variables such as local temperature, age, sex, origin, and pregnancy status to determine the optimal combination of parameters for sheep growth in our dataset. The results have shown that moving the old sheep from the steppe to the valley resulted in an increase of an average of 1 kg in weight, but their offspring had an asymptotic weight of 65 kg, 17 kg more than their mothers. The optimum temperature for the growth rate was 15.7+/-0.56 C and 8.7+/-6.3C for the asymptotic weight.